Pendidikan Iman dalam Budaya Digital: Tantangan dan Peluang Katekese bagi Generasi Z - Floriana Doa; Monica Innanda Chiaralazzo; Intansakti Pius X (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This article, The development of digital technology has brought about significant changes in human life, including in the way we communicate, obtain information, and live our lives of faith. The emergence of the digital generation, particularly Generation Z, demands that the Church adapt its faith education model to remain relevant to the times. This article aims to reflect on the influence of the digital generation on faith education and analyze the challenges and opportunities for catechesis in the era of technological disruption. This research uses a qualitative approach with a library research method, namely through the review of various scientific literature, journals, and Church documents related to the digital generation, faith education, and catechesis. The results of the discussion indicate that digital culture presents challenges in the form of an instant culture, unverified information flows, individualism, and a decline in the depth of spiritual reflection. However, digital technology also opens up significant opportunities for the Church to implement catechesis more broadly, creatively, interactively, and easily accessible through social media, podcasts, online videos, and digital communities. Therefore, the Church needs to renew its catechesis model through a dialogical, participatory, and contextual approach without changing the content of faith teachings. Digital catechesis should continue to direct people to a real encounter with God, others, and the Church community. Thus, the digital generation is a new opportunity for the Church to proclaim the Gospel amidst changing times.